The design and sustainability of renewable energy incentives : an economic analysis - Meier, Peter, 1942- (Directions in development (Washington, D.C.). Energy and mining., 2014)
The novelty of this work is the fact that it introduces a rigorous and objective economic perspective of current renewable energy support mechanisms and an empirical analysis of the strengths and weaknesses of these mechanisms, which is much needed in a debate often dominated by widespread misconceptions. The economic rationale for renewable energy is straightforward: the optimum amount of renewable energy for grid-connected generation is given by the intersection of the renewable energy supply curve with the avoided cost of thermal electricity generation. The proposed analytical framework: (i.